Lithium-CO2 batteries and beyond - Pathak, Anil D.; Adhikari, Pashupati R.; Choi, Wonbong (Frontiers in Energy Research, 2023)
Li-CO2 batteries with a theoretical energy density of 1876 Wh kg-1 are attractive as a promising energy storage strategy and as an effective way to reduce greenhouse gas emissions by CO2 reduction and the formation of discharge product Li2CO3 and carbon. This article provides critical perspectives on the development of Li-CO2 batteries as well as a description of current issues and challenges associated with cathode catalysts, electrolyte, and anode for Li-CO2 batteries. Furthermore, the development and deployment of materials to overcome these challenges of Li-CO2 batteries are discussed briefly. Finally, a systematic analysis of beyond Li-CO2 batteries (other Metal-CO2 batteries) as a potential research direction in the development of energy storage and CO2 fixation and utilization in practical applications is provided.